Neural Correlates of Beauty - Kawabata, Hideaki; Zeki, Semir (Journal of neurophysiology, 2004)
Wellcome Department of Imaging Neuroscience, University College, London WC1E 6BT, United Kingdom Submitted 18 July 2003; accepted in final form 20 November 2003 We have used the technique of functional MRI to address the question of whether there are brain areas that are specifically engaged when subjects view paintings that they consider to be beautiful, regardless of the category of painting (that is whether it is a portrait, a landscape, a still life, or an abstract composition). Prior to scanning, each subject viewed a large number of paintings and classified them into beautiful, neutral, or ugly. They then viewed the same paintings in the scanner. The results show that the perception of different categories of paintings are associated with distinct and specialized visual areas of the brain, that the orbito-frontal cortex is differentially engaged during the perception of beautiful and ugly stimuli, regardless of the category of painting, and that the perception of stimuli as beautiful or ugly mobilizes the motor cortex differentially. Address reprint requests and other correspondence to: S. Zeki (E-mail: zeki.paatucl.ac.uk ).